LOGISTICS IN THE CONTEMPORARY WORLD: PECULIARITIES IN RUSSIA AND KEY PROBLEMS - V. Kolobkova (Publishing House of the State University of Management, 2017)
In the article the urgency majorof logistics in modern заключениconditions, theoretical логистическиbases of the потребителямterm «Logistics» is процессconsidered. The логистикиtasks of logistics магистратурыare defined, озданиlogistics infrastructure логисти analysis is carried стремятся out and промышленностиthe necessary услугmeasures are компанийproposed to improve развитыхthe development эффективностиof the logistics сценариindustry.